SUMUR RESAPAN AIR LIMBAH KAMAR MANDI UNTUK KESEIMBANGAN PERMUKAAN AIR TANAH DI DAERAH PERMUKIMAN (Studi Kasus Di Perumahan RT. II, RT. III, dan RT. IV Perumnas Lingkar Timur Bengkulu) - Anggun Lia Anestri; Agustin Gunawan; Besperi Besperi (Inersia: Jurnal Teknik Sipil, 2019)
omestic waste water from bathroom, that generally being a waste water, can be used to balance the ground water surface.Utilization of bathroom waste water is done by making the  infiltration well. This study aimed to quantify the debit of resulted bathroom waste water and to design the bathroom waste water infiltration well. The experiment was conducted in Housing RT. II, RT. III, and RT. IV Permunas Lingkar Timur of Bengkulu that has number of house of153 units and number of inhabitant as much as 701 people. The research used survey methods such as questionnaires / interviews and percolation test to obtain the required data. Based on the data and analysis of calculation according to the Sunjoto method, concluded that the debit of bathroom waste water for RT. II, RT. III, and RT. IV was consecutive 3.38x10-5 m3/s, 9.688x10-5 m3/s, 0.0001558 m3/s. The number of produced infiltration well total 33 wells whichis 4 wells for RT. II, 5 wells for RT. III, and 24 wells for RT. IV. Each of infiltration well haddifferent dimensions in accordance with the need.